2018
DOI: 10.1039/c7cp07811k
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced hopping model for long-range triplet excitation energy transfer in DNA

Abstract: We present a theoretical model for long-range triplet excitation energy transfer in DNA sequences of alternating adenine-thymine steps. It consists of thermally induced hops through thymine bases. Intrastrand hops between thymines separated by an AT step are preferred to interstrand hops between thymines in consecutive steps. Our multi-step mechanism is consistent with recent results (L. Antusch, N. Gass and H.-A. Wagenknecht, Angew. Chem., Int. Ed., 2017, 56, 1385-1389) describing a shallow dependence of trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A rather large panel of experimental data are available to assess the decay channels of 3 T leading either to the population of the singlet ground state or to the formation of photodamages, for isolated nucleotides or in single-stranded DNA thymines (21,22). In parallel, several computational studies have considered 3 T embedded in B-DNA, to assess characteristic energies and lifetimes for triplet-triplet energy transfer, either with photosensitizers (23) or along thymine stacks (24,25). In 2011, the characteristic time for triplet migration was estimated at 6.4 ns by semi-empirical quantum chemical methods coupled to classical molecular-dynamics simulations (26).…”
Section: Introductionmentioning
confidence: 99%
“…A rather large panel of experimental data are available to assess the decay channels of 3 T leading either to the population of the singlet ground state or to the formation of photodamages, for isolated nucleotides or in single-stranded DNA thymines (21,22). In parallel, several computational studies have considered 3 T embedded in B-DNA, to assess characteristic energies and lifetimes for triplet-triplet energy transfer, either with photosensitizers (23) or along thymine stacks (24,25). In 2011, the characteristic time for triplet migration was estimated at 6.4 ns by semi-empirical quantum chemical methods coupled to classical molecular-dynamics simulations (26).…”
Section: Introductionmentioning
confidence: 99%
“…The charge migration (CT) toward π-stacked base pairs (BP) is sensitive to its structural and electronic changes. Voityuk [34,35] has shown that the hole migration process between stacked base pairs in ds-DNA can take place between triplet excited states [36][37][38]. From this point, the 8,7-dihydro-8-oxo-2 -deoxyguanosie, which shows a lower ionization energy/potential (6.94 eV [22,39]) than its precursor dG, can easily be oxidized and constitutes an endpoint for cation radical migration, which leads to a) protection of the rest of ds-oligo against oxidation, and b) flagging the lesion for glycosylase movements.…”
Section: Introductionmentioning
confidence: 99%
“…Ab-initio techniques are impractical to treat this problem, and even hybrid methods are challenging: Explicit atomistic calculations at the level of molecular dynamics (for sampling configurations), combined with quantum mechanics/molecular mechanics (QM/MM) methodologies are limited to short sequences and short evolution time [37][38][39][40] . This challenge calls for the development of coarse grained models with perturbative methods [41][42][43][44] , model-system computational schemes 40 , and phenomenological approaches 31,35,36,45 . For example, the fluctuating nuclear environment of DNA can be described by adding noise terms to the static, purely electronic Hamiltonian.…”
Section: B Landauer Büttiker Probe Simulationsmentioning
confidence: 99%